2020
DOI: 10.3390/s20020425
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelastic Humidity Sensors with TiO2 Nanotube Sensing Layers

Abstract: In this study, TiO2 nanotubes (TiO2-NTs) are coated with a drop-casting method on Fe40Ni38Mo4B18 amorphous ferromagnetic ribbons and the humidity response of the prepared magnetoelastic sensors (MES) is investigated. The synthesis of TiO2-NTs is performed using a hydrothermal process. Sample characterization is carried out using X-ray diffraction and scanning electron microscopy. The results show that the sensors can measure moisture values in the range of 5% to 95% with very high precision and very low hyster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Functional coatings have been applied to magnetoelastic sensors, facilitating the monitoring of various physical, chemical, and biological parameters and processes. Examples include humidity monitoring with titanium dioxide nanotubes, [20][21][22][23][24] toluene detection with metal-organic chemical frameworks, 2 heavy metal sensing with graphene oxide, 7 and even viral and bacterial detection with bioreceptors. 7,[10][11][12][13][14][15][16]25,26 Recent studies have suggested the possibility of enhancing the sensor's sensitivity by adjusting the degree of modification in different regions of the sensor.…”
Section: Introductionmentioning
confidence: 99%
“…Functional coatings have been applied to magnetoelastic sensors, facilitating the monitoring of various physical, chemical, and biological parameters and processes. Examples include humidity monitoring with titanium dioxide nanotubes, [20][21][22][23][24] toluene detection with metal-organic chemical frameworks, 2 heavy metal sensing with graphene oxide, 7 and even viral and bacterial detection with bioreceptors. 7,[10][11][12][13][14][15][16]25,26 Recent studies have suggested the possibility of enhancing the sensor's sensitivity by adjusting the degree of modification in different regions of the sensor.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of such vibration depend on the external variable magnetic field, the strip dimensions and its mass distribution. Thus, the accumulation on the strip surface of substances such as biological agents [6], air pollutants [7], volatile organic compounds [8], H 2 O [9] or H 2 O 2 [10], which bind to suitable surface coating, will change its mass distribution and consequently its vibration characteristics (resonant frequencies). Hence, shifted resonant frequencies indicate a significant concentration of substances on it and, accordingly, the environment.…”
Section: Introductionmentioning
confidence: 99%
“…This exciting and rich set of material properties has made TiO 2 a valuable candidate for applications in many fields, as well as for fundamental science investigations. To date, the market demand on TiO 2 -based devices for photocatalysis [1][2][3][4], sensors [5,6], optical reflective coatings for highly innovative 2 of 18 applications [7,8] (innovative mirrors for gravitational wave interferometers, among the others [9][10][11][12]), solar cells [13][14][15], metal insulator semiconductor industry [16], self-cleaning application [17][18][19], water purification processes [20], has been systematically growing, especially for thin films and nanostructures. In addition, a constant effort has been made in setting up reliable computational techniques, mainly based on density functional theory (DFT), to predict and describe the properties of TiO 2 , not only in its crystalline forms, but also in the amorphous phase, as well as to simulate the amorphous to crystalline phase transition [21][22][23].…”
Section: Introductionmentioning
confidence: 99%